A refined method for estimating capsule crops in individual jarrah (Eucalyptus marginata) crowns. Issue 3 (2nd July 2016) - Cargill, Jeffry; Van Etten, Eddie J.B.; Whitford, Kim R.; McCaw, Lachlan W.; Stock, William D.
ABSTRACT: An accurate measure of the number of capsules in the crowns of jarrah ( Eucalyptus marginata ) trees is needed to assess the potential for seedling regeneration prior to silvicultural treatment in jarrah forests. The current method of estimating capsule crops on jarrah trees uses stem diameter and estimates of capsule density in the crown, but has not been fully validated. In this study, we sought to develop an accurate and practical method of assessing capsule crops in the crowns of individual jarrah trees. We did this by measuring a number of tree characteristics prior to felling them. A total of 24 trees were selected, spanning a range of sizes and crown conditions, and the total number of capsules was counted for each tree. Multiple linear regression was used to model capsule number against various combinations of eight different tree/crown variables, with model fit compared using an adjusted coefficient of determination (adjR 2 ). The final model recommended for field use included three easily measured variables (stem diameter, subjective assessment of capsule density, and subjective assessment of capsule clump distribution in the crown) and had a high degree of predictability (adjR 2  = 0.83), which was the same as that of the full model. This method substantially improved estimates of crown capsule numbers compared with the method currently used (adjR 2 increased from 0.29 to 0.83), which tended to underestimate canopy capsule numbers.